Time Varying Government Spending Multipliers : Evidence from the US data - Focht, Daniel; Maršál, Aleš; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This paper estimates the size of the government spending multiplier over different states of the economy. Previous research came with two contradictory conclusions. Part of the literature argues that the spending multiplier is larger during recession and zero-lower bound periods, while the second one concludes that it remains constant. First, a summary of the relevant literature is presented, outlining different types of used methodological approaches and estimated size of the multiplier. We build a model estimated using local projections by Jorda for the period 1889 to 2016 to estimate government spending multipliers over different states of the economy. Our results show that the spending multiplier remains constant over different states of the economy.
Vedoucí práce: Aleš Maršál
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses